PARTISIPASI POLITIK DALAM KONSEPSI TEORI PILIHAN RASIONAL JAMES S COLEMAN - Sastrawati, Nila (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2020)
Social action is an important aspect in analyzing behavior, including in analyzing the political participation of individuals and society. Diverse forms of political participation indicate that individuals make choices of political participation based on subjective considerations with reference to costs and rewards. In the conception of Rational Choice Theory from James S. Coleman, there are 2 main essences, namely actors and resources. Actors as actors of participation, have the power to use resources, including external resources or political modalities so that the actors’ political objectives are achieved.